2019
DOI: 10.1155/2019/9213074
|View full text |Cite
|
Sign up to set email alerts
|

Mean Platelet Volume (MPV): New Perspectives for an Old Marker in the Course and Prognosis of Inflammatory Conditions

Abstract: Platelet size has been demonstrated to reflect platelet activity and seems to be a useful predictive and prognostic biomarker of cardiovascular events. It is associated with a variety of prothrombotic and proinflammatory diseases. The aim is a review of literature reports concerning changes in the mean platelet volume (MPV) and its possible role as a biomarker in inflammatory processes and neoplastic diseases. PubMed database was searched for sources using the following keywords: platelet activation, platelet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
396
2
19

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(426 citation statements)
references
References 118 publications
9
396
2
19
Order By: Relevance
“…Similarly, O'Malley et al [20] found greater MPV values in patients with acute ischemic stroke than in controls. Conversely, Cho et al did not find any significant difference between patients and controls in relation to MPV values, [21] but most of the studies proved that MPV levels were higher in stroke patients [19].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Similarly, O'Malley et al [20] found greater MPV values in patients with acute ischemic stroke than in controls. Conversely, Cho et al did not find any significant difference between patients and controls in relation to MPV values, [21] but most of the studies proved that MPV levels were higher in stroke patients [19].…”
Section: Discussionmentioning
confidence: 91%
“…Increment in the mean platelet volume (MPV) level has been observed in patients with stroke [17] and acute myocardial infarction [18] than in control subjects. Aleksandra Korniluk et al [19] found that MPV and MPV/PC ratio was significantly higher in patients presenting with cerebrovascular stroke compared to a control group. Similarly, O'Malley et al [20] found greater MPV values in patients with acute ischemic stroke than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, a high level of peripheral NLR indicates the severity of the clinical course. Peripheral MPVLR represents the ratio of mean platelet volume to lymphocyte count, and high peripheral MPV values have been found in a variety of inflammatory diseases (32). Elevated MPVLR was shown in previous studies to predict the poor prognosis of patients with cardiovascular disease, especially for coronary heart disease (25,33).…”
Section: Discussionmentioning
confidence: 98%
“…Platelets also support leukocytes to eliminate bacterial infections via direct contact, encapsulation of bacteria, and release of reactive oxygen species and platelet microbicidal proteins (PMP). 13 The mechanism of changing platelet function in sepsis is still unclear. Platelet shape changes from discoid to spherical with pseudopodia during activation.…”
Section: Discussionmentioning
confidence: 99%